Immunohistochemical expression of progesterone receptors in adenoid cystic carcinoma and pleomorphic adenoma of salivary glands - Eslami M; Eshghyar N; Ensani F; Seifi S (Tehran University of Medical Sciences, 2006)
Background and Aim: The hormone receptor status in breast cancer has been pivotal in determining the likelihood of response to hormonal manipulation. Tumors which are both estrogen and progesterone receptor positive are much more likely to respond to anti-hormone therapy than negative tumors. There is well-established similarity between breast tissue and salivary glands. The aim of this study was to evaluate the progesterone receptor expression in pleomorphic adenoma and adenoid cystic carcinoma of salivary glands. Materials and Methods: In this descriptive study, immunohistochemical staining with progesterone antibody was performed on 14 pleomorphic adenoma (PA) and 15 adenoid cystic carcinoma (ACC) paraffin blocks. The percentage of positive cells was determined using an eye piece graticule. Immunoreactivity was categorized as either positive (reactivity more than 5%) or negative (reactivity less than 5%). In addition the existence of progesterone receptor in tumor cells, stromal cells (fibroblasts), inflammatory cells and salivary glands around tumors was evaluated. Data were analyzed with T and Mann Whitney U tests with p<0.05 as the limit of significance. Results: Immunohistochemical staining for progesterone receptor was negative in 15 ACC and 13 PA. Only one case of PA showed immunoreactivity for progesterone receptor. Also, 12 normal salivary glands around tumor were positive. Inflammatory cells, endothelial cells and fibroblasts did not show immunoreactivity in most cases. Conclusion: The results indicate the lack of progesterone receptor expression in ACC and PA of salivary glands.